A Comunidade de Prática como Ferramenta da Criação de Conhecimento no Contexto do Agronegócio - Erlaine Binotto (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2007)
Ahead of the interest in Communities of Practice (CoPs) study, having knowledge management as scenery this paper aims to identify the role of Communities of Practice for the occurrence of knowledge creation on farm in Brazil, a cooperative reality, and Australia, where the businesses are lead individually. It`s a descriptive research with qualitative and quantitative data. The case studies used documentation, observation in loco, questionnaire, interview and focus group instruments. The results have demonstrated that the cultural aspects and relation styles have seemed to exert strong influence over the occurrence of changes of information and to broaden the effects of CoPs, which may support knowledge creation. CoPs are not an organized technological process, but a social and cognitive process and, like this, its formation does not seem to be dependent only on technology. Then, groups that have opportunities to discuss help people to know each other and assimilate knowledge allowing that all ask and relate something new that have had chance to know and the same time revised their points of view.